Al–X and Cu–X [X = Li, Na] nano-alloys: a low cost alternative to silver and gold nanoparticles for plasmonic applications. Issue 72 (6th August 2015) - Debnath, Shaikat; Said, Suhana Mohd; Rabilloud, Franck; Chatterjee, Abhijit; Rashid, Mohammad Mamunur; Mainal, Azizah
<x xml:space="preserve">Abstract</x> Single X atom (X = Li and Na) is doped into Cu and Al to form Cu12X and Al12X clusters. The Al12X clusters exhibit remarkable optical absorption properties in the range of 3–11 eV.